2018
DOI: 10.3389/fnint.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Different Behavioral Experiences Produce Distinctive Parallel Changes in, and Correlate With, Frontal Cortex and Hippocampal Global Post-translational Histone Levels

Abstract: While it is clear that behavioral experience modulates epigenetic profiles, it is less evident how the nature of that experience influences outcomes and whether epigenetic/genetic “biomarkers” could be extracted to classify different types of behavioral experience. To begin to address this question, male and female mice were subjected to either a Fixed Interval (FI) schedule of food reward, or a single episode of forced swim followed by restraint stress, or no explicit behavioral experience after which global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 72 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…During recent years, growing body of evidence has emerged to suggest sex differences in regionally specific recruitment of histone PTMs and histones modifying enzymes involved in regulating transcription of genes important for learning and/or memory (Keiser & Wood, 2019). Interestingly, a recent study revealed that different behavioral experiences produced sex-specific differences of global histone H3K9 acetylation and methylation patterns, both within and across the dorsal HPC and frontal cortex (Sobolewski, Singh, Schneider, & Cory-Slechta, 2018). Furthermore, higher levels of both HDAC activity and/or DNA methyltransferase 1 content have been reported in the HPC and cortices of females compared to males, indicators of increased transcriptional activity repression (Elsner, Cechinel, de Meireles, Bertoldi, & Siqueira, 2018;Tsai, Grant, & Rissman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, growing body of evidence has emerged to suggest sex differences in regionally specific recruitment of histone PTMs and histones modifying enzymes involved in regulating transcription of genes important for learning and/or memory (Keiser & Wood, 2019). Interestingly, a recent study revealed that different behavioral experiences produced sex-specific differences of global histone H3K9 acetylation and methylation patterns, both within and across the dorsal HPC and frontal cortex (Sobolewski, Singh, Schneider, & Cory-Slechta, 2018). Furthermore, higher levels of both HDAC activity and/or DNA methyltransferase 1 content have been reported in the HPC and cortices of females compared to males, indicators of increased transcriptional activity repression (Elsner, Cechinel, de Meireles, Bertoldi, & Siqueira, 2018;Tsai, Grant, & Rissman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“… Data from [ 42 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] and cited literature. F = female; M = male; UGT = UDP-glucuronosyl-transferase; SULT = sulfotransferase; SLC = solute carrier family; MRP = multidrug resistance protein; Oatp = organic anion-transporting polypeptide.…”
Section: Figurementioning
confidence: 99%